2015
DOI: 10.1186/s40494-015-0060-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel conservation treatment of stone monuments with bioactive nanocomposites

Abstract: In this study a conservation treatment of stone monuments meant for consolidation, protection, and inhibition of biofilm formation is proposed. The method is developed as a part of a systematic investigation aimed at producing nanocomposite coatings able to exert a marked biological activity over a long period of time thanks to their peculiar structure. Zinc oxide nanoparticles, synthesised by means of simple and reproducible electrochemical procedures, are embedded in commercially available and commonly used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 30 publications
(49 reference statements)
0
30
0
Order By: Relevance
“…Semiconductor metal oxide nanostructures, and specifically ZnO ones, have received a great amount of interest in many areas due to their unique physical, chemical and optical properties [1]. Moreover, ZnO nanomaterials are well-known antimicrobial agents [2], which can be employed in several fields where pathogen spreading should be inhibited [3][4][5]. Besides the many physical [6][7][8] and chemical [9][10][11] methods for the production of such materials, scientific research has recently focused on green and simple electrochemical approaches [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor metal oxide nanostructures, and specifically ZnO ones, have received a great amount of interest in many areas due to their unique physical, chemical and optical properties [1]. Moreover, ZnO nanomaterials are well-known antimicrobial agents [2], which can be employed in several fields where pathogen spreading should be inhibited [3][4][5]. Besides the many physical [6][7][8] and chemical [9][10][11] methods for the production of such materials, scientific research has recently focused on green and simple electrochemical approaches [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of the penetration depth and homogeneous application of nanoconsolidants remain some of the most important requirements, together with avoiding modification of the breathability of the substrate and flaking of the surface or detachment, among others. At the same time, chromatic changes caused by either nanolime concentrations or by the inclusion of NPs in the silica matrices have been reduced but not overcome . Moreover, the solvents and surfactants are potentially hazardous for living organisms and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Electrochemically synthesized zinc oxide (ZnO) NPs, incorporated in commercial consolidant/water repellent TEOS‐based products, form a material that is expected to display long‐term biocide activity. Nevertheless, chromatic changes, although reduced, still remain as the main issue for application of this nanocomposite …”
Section: Organic–inorganic Nanostructured Materials: Alkoxysilanesmentioning
confidence: 99%
“…Thus, I.D. Van der Werf et al (147) demonstrated that higher ZnO nanoparticles loadings could be achieved without affecting the color of the stone substrates. Recently, Ditaranto et al (148) developed bioactive nanocomposite systems composed by a water repellent/ consolidant product and zinc oxide nanoparticles in various %w/w concentrations for the protection of stone heritage.…”
Section: Antimicrobial Stone Coatingsmentioning
confidence: 99%